INVENTARISASI SERANGGA TANAH DI LAHAN BEKAS KEBAKARAN DESA TANJUNG BATU KECAMATAN TANJUNG BATU, KABUPAEN OGAN ILIR DAN SUMBANGANNYA PADA PEMBELAJARAN BIOLOGI SMA - Zulkarnain Z (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2018)
Research about inventory of soil insects on the land of fired at Tanjung Batu village, Tanjung Batu districts, OI regency and its contribution to biology learning in high school has been done, this study armed to knowing the variety of insects and composition from insects which are founded on the land of fired and the land not fired. This study used Purposive Sampling method. Insects sample collected by directly catched and barless tulgreen on December 2016. Insects was catched and collected from 10 plots which consistant 2 location, on the land of fired and not fired have 5 plots each. Data was analysed descriptively. Based on the result of research study. Insects that founded classify by 6 order and 10 family, such as Coleoptera; Scarabaeniae, Hybosorinae, Buprestidae, Curcolionidae, Clambidae, Diplura; Anajapygidae, Blattaria; Blattidae, Isoptera, Hymenoptera; Formicidae, and Collembola. 398 of the insects from the land of fired and not fired. The result also contributed as references to learning material Biology X class about Biodiversity Basic Competence 3.2, Analyzing data observation about the variant of Biodiversity (gen, variety and Ecosystem) in Indonesia. Keywords : Soil Insects, land of fired and land not fire